Expressive Freedom and Ethical Responsibility at Canadian Universities - Thieme, Katja (Atlantis)

(untitled) (Mount Saint Vincent University, 2023)
This article reviews recent government incursions on questions of free speech at universities and colleges in Ontario and Alberta and presents the challenge they pose to university autonomy. Inherent in university autonomy is the possibility—or the obligation—that universities make decisions based on ethical responsibilities that can extend beyond the limits of current law. As a case study of university autonomy in matters of expressive freedom, I highlight events at the University of British Columbia, which leads me to a discussion of how questions of ethical responsibility have been raised particularly in relation to the speech protection of transgender members of the university. A central issue is the need for universities to adjudicate when free speech rights meet related responsibilities with which they can conflict. I detail how, for instance, the invitation of some anti-trans speakers can pose such a conflict and should lead university communities to consider adjusting their responses in extreme cases so as to be able to more autonomously regulate hateful speech beyond applicable law.